Strategies in translation of slangs French to Malay in the film Les Intouchables (2012) - Abdul Halim, Hazlina (ASR Research India, 2022)
Slangs are one of the challenges for translators and subtitlers to convey the most accurate meaning due cultural differences between the source and the target language. Therefore, this research sets out to investigate the strategies used to translate slangs in the French film Les Intouchables. The data for this study are from the dialogues in French and their subtitles in Malay. The research uses qualitative method of data analysis by applying the classification of slang by Matiello (2008) to identify the slangs and by adapting translation techniques by Baker (1992). The results found 80 slangs which were classified as 47 general slangs and 33 specific slangs. It was also found that most of the slangs were translated using equivalent expression in the target language. It is hope that this research will attract and boost other translation research involving languages with different cultures such as French and Malay.